2010
DOI: 10.1002/bin.312
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing physiological measures to facilitate phobia treatment with individuals with autism and intellectual disability: A case study

Abstract: Despite the conceptualization of phobic fear as a multi-factorial response, the measurement and treatment of phobias is often not comprehensive. The extant literature on the treatment of phobias for individuals with intellectual disabilities has exclusively focused on indices of behavioral avoidance. The present study demonstrates the treatment of behavioral avoidance and physiological reactivity in a child diagnosed with autism, intellectual disability, and a dog phobia. The results indicate that the individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…It is of interest to note that there were multiple studies that almost met full inclusion criteria for the review. For example, five studies in this process were identified as treating anxiety in individuals with LFA, but the within-subject design procedures did not meet full inclusion criteria because of a lack of experimental control (Chok, Demanche, Kennedy, & Studer, 2010;Ellis, Ala'i-Rosales, Glenn, Rosales-Ruiz, & Greenspoon, 2006;Grider, Luiselli, & Turcotte-Shamski, 2012;Ricciardi, Luiselli, & Camare, 2006;Slifer et al, 2011). Another within-subject study on increasing tolerance to injections omitted a baseline phase and did not attribute the symptoms to anxiety; otherwise, it would have met full inclusion criteria (Birkan, Krantz, & McClannahan, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…It is of interest to note that there were multiple studies that almost met full inclusion criteria for the review. For example, five studies in this process were identified as treating anxiety in individuals with LFA, but the within-subject design procedures did not meet full inclusion criteria because of a lack of experimental control (Chok, Demanche, Kennedy, & Studer, 2010;Ellis, Ala'i-Rosales, Glenn, Rosales-Ruiz, & Greenspoon, 2006;Grider, Luiselli, & Turcotte-Shamski, 2012;Ricciardi, Luiselli, & Camare, 2006;Slifer et al, 2011). Another within-subject study on increasing tolerance to injections omitted a baseline phase and did not attribute the symptoms to anxiety; otherwise, it would have met full inclusion criteria (Birkan, Krantz, & McClannahan, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Included studies were assessed to determine whether challenging behaviors were reported to occur in the presence of the targeted fear or phobia. Twelve of the 16 studies reviewed (Chok et al 2010;Davis et al 2007;Ellis et al 2006;Gillis et al 2009;Jackson and King 1982;Koegel et al 2004;Love et al 1990;Luiselli 1978;Rapp et al 2005;Ricciardi et al 2006;Schmidt et al 2013;Shabani and Fisher 2006) reported the occurrence of challenging behavior in the presence of the feared stimulus prior to intervention. Most common were disruptive vocalizations and verbalizations, such as screaming or crying, which were elicited in the presence of the feared or phobic stimulus in 11 studies (Chok et al 2010;Ellis et al 2006;Gillis et al 2009;Jackson and King 1982;Koegel et al 2004;Love et al 1990;Luscre and Center 1996;Rapp et al 2005;Ricciardi et al 2006;Schmidt et al 2013;Shabani and Fisher 2006).…”
Section: Association Between Fears or Phobias And Challenging Behaviormentioning
confidence: 99%
“…Twelve of the 16 studies reviewed (Chok et al 2010;Davis et al 2007;Ellis et al 2006;Gillis et al 2009;Jackson and King 1982;Koegel et al 2004;Love et al 1990;Luiselli 1978;Rapp et al 2005;Ricciardi et al 2006;Schmidt et al 2013;Shabani and Fisher 2006) reported the occurrence of challenging behavior in the presence of the feared stimulus prior to intervention. Most common were disruptive vocalizations and verbalizations, such as screaming or crying, which were elicited in the presence of the feared or phobic stimulus in 11 studies (Chok et al 2010;Ellis et al 2006;Gillis et al 2009;Jackson and King 1982;Koegel et al 2004;Love et al 1990;Luscre and Center 1996;Rapp et al 2005;Ricciardi et al 2006;Schmidt et al 2013;Shabani and Fisher 2006). Elopement, or attempts to elope, was described by 10 studies (Chok et al 2010;Gillis et al 2009;Jackson and King 1982;Koegel et al 2004;Love et al 1990;Luiselli 1978;Rapp et al 2005;Ricciardi et al 2006;Schmidt et al 2013;Shabani and Fisher 2006).…”
Section: Association Between Fears or Phobias And Challenging Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Reinforcement is especially useful for those with low motivation, which is a common problem in those with ID/DD, as insight is particularly poor (Koegel et al 2010). RP has also been used in several uncontrolled case studies and open clinical trials by several researchers (e.g., Chok et al 2010;Luiselli 1977;Obler and Terwilliger 1970;Shabani and Fisher 2006) to treat a variety of fears including those of dogs, blood-injection-injury, toileting, and buses.…”
Section: Reinforced Practice (Rp)mentioning
confidence: 99%